Virtual listening service in Brazilian higher education institutions - Scroferneker, Cleusa Maria Andrade (Organicom, 2010)
This text presents the results of the first two phases of a research on the different ways proposed by universities to listen “virtually” to (and interact with) distinct public segments, particularly the ones identified as Talk to us, Contact, Contacts and/or Listener’s office. The interest in investigating this new “listening”, named in the project as virtual “listener’s office”, is due to the realization that at present these new types of “interactivity”, which more and more are seen on university sites/portals, are one of the main options for relationship and communication, by “virtualizing” speaking and listening.